Enhancement of interfacial bonding strength of SMA smart composites by using mechanical indented method. (1st December 2016) - Yuan, Guoqing; Bai, Yanjie; Jia, Zhemin; Hui, David; Lau, Kin-tak
Abstract: Shape memory alloy (SMA) wire reinforced polymer-based composites have been recognized as a new type of smart materials. However, their weak interfacial bonding strength between the wire and its surrounding matrix limits its applications in many engineering industries. In this paper, a new method called "mechanical indentation" is introduced to effectively enhance the interfacial bonding strength of SMA composites. According to the results from a wire pullout test, the interfacial bonding strength of an indented SMA wire composite increased by 4.48–8.58 times as compared with a hand-sanded SMA wire composite at a room temperature condition. Two different sizes of indentations, sparse and dense indentations were studied in detail and the results indicated that the dense indented SMA wire had a better performance in terms of tensile and recovery properties, than that of the sparse indented wire. Furthermore, the interface between the dense indented wire and vinyl-ester (VE) matrix demonstrated a better restoration performance during a repeated loading-and-unloading process at room temperature condition.